Saying the other: the poetics of personification in late antique epic - Greensmith, E (Cambridge University Press, 2022)
This chapter treats allegory in the Posthomerica in light of late antique thinking on personification. Tracing Quintus’ deployment of the technique, it centres on the shield of Achilles, which contains the fullest personification allegory: the Mountain of Arete. Scholars have focused on the literary-philosophical aspects of this image. I argue that Quintus uses personification self-consciously as a literary device. Drawing on contemporary conceptions of personification from both the Greek and Latin traditions – rhetorical treatises, school exercises and literary works (particularly Prudentius’ Psychomachia, which applies personification full-scale into hexameter verse) –this chapter shows how the Posthomerica reflects ideas in these texts about the inherently duplicitous nature of this mode of writing. Highlighting the tensions in his allegorical configurations, Quintus reveals a sophisticated understanding of personification as a productive but problematic system of divergence and convergence between different worlds and perspectives. By so doing, he advertises limits and challenges of his own poetic creation – a text both rooted in the Homeric past and a product of its time.